2017
DOI: 10.1016/j.alcohol.2017.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Working memory over a six-year period in young binge drinkers

Abstract: Adolescence and early adulthood are periods of particular vulnerability to the neurotoxic effects of alcohol. Young people with alcohol-use disorders display deficits in working memory (WM). This function is supported by the prefrontal cortex, a late-maturing brain region. However, little is known about the progression of cognitive dysfunctions associated with a binge-drinking (BD) pattern of alcohol consumption among non-clinical adolescents. The objective of this study was to analyze the relationship between… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 48 publications
1
27
0
Order By: Relevance
“…Furthermore, the repetitive data collection allowed the study of drinking patterns in addition to commonly reported average consumption levels. This is relevant since alcohol-drinking pattern may be an important determinant for the harmful effects of drinking, such as binge drinking [11,12,20].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, the repetitive data collection allowed the study of drinking patterns in addition to commonly reported average consumption levels. This is relevant since alcohol-drinking pattern may be an important determinant for the harmful effects of drinking, such as binge drinking [11,12,20].…”
Section: Discussionmentioning
confidence: 99%
“…However, the online cognitive tests performed at home may not have been sensitive enough to pick up differences in cognitive performance associated with alcohol consumption.Nutrients 2020, 12, 200 2 of 12 developmental shifts, making the reward system particularly sensitive to alcohol in ways that could promote excessive consumption [7].Cross-sectional studies in young adult binge drinkers showed impaired executive cognitive performance and brain development compared to nonbinge-drinking control subjects, as suggested by electrophysiological differences during the execution of a visual task with a high working memory load [8][9][10]. Longitudinal observational studies, in which binge-drinking adolescents were followed into adulthood, showed that long-term excessive drinking was associated with negatively affected working memory [11] and verbal memory and learning [12] as opposed to nonbinge-drinking adolescents. Similarly, college students who reported regular binge drinking performed poorer on planning and spatial working memory tasks as compared to nondrinking controls [13].In the general population, only a few small-scale longitudinal studies on alcohol consumption and cognitive performance have been performed.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast, heavy drinkers had reduced capacities to inhibit a prepotent response (Ahmadi et al, 2013;Dager et al, 2013). Numerous functional imaging studies converge to indicate that binge drinking affects functional organization of working memory processes, disrupts executive functions and triggers impulsive behaviours (Crego et al, 2010;Lyvers et al, 2012;Gil-Hernandez & Garcia-Moreno, 2016;Carbia et al, 2017).…”
Section: In Humansmentioning
confidence: 99%